2009
DOI: 10.5424/sjar/2009074-1104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced doses of mesosulfuron + iodosulfuron to control weeds in no-till wheat under Mediterranean conditions

Abstract: Field experiments were carried out over three years (2004-05, to 2006-07) to study the efficacy of a post-emergence dual-purpose herbicide (mesosulfuron -methyl (3%) + iodosulfuron -methyl -sodium (0.6%) + mefenpyr -diethyl (9%) to control Lolium rigidum Gaud. and broad-leaved weeds in no-till wheat (Triticum aestivum L.). A ready herbicide mixture was used at three doses (6+1.2, 9+1.8 and 12+2.4 g a.i. ha -1 ) on two dates (beginning of tillering for L. rigidum and 2-3 pair of leaves for broad-leaved weeds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Increasing the dose of herbicide application from 1.5 to 3 li/ha increased weed control and 3.5 li/ha controlled weeds by 100% (Figure 3). In another experiment [15], it was concluded that although the full dose was better, reduced doses were also effective and controlled weeds desirably. They suggested that to increase the efficiency of reduced doses, herbicide must be applied at early growth stages of weeds.…”
Section: Resultsmentioning
confidence: 95%
“…Increasing the dose of herbicide application from 1.5 to 3 li/ha increased weed control and 3.5 li/ha controlled weeds by 100% (Figure 3). In another experiment [15], it was concluded that although the full dose was better, reduced doses were also effective and controlled weeds desirably. They suggested that to increase the efficiency of reduced doses, herbicide must be applied at early growth stages of weeds.…”
Section: Resultsmentioning
confidence: 95%
“…The other 6 treatments, including mesosulfuron-methyl + iodosulfuron-methyl-sodium, were excellent on many annual broadleaf weed species, but less effective against milk thistle (S. marianum), as indicated by higher weed biomass (Table 3). In Portugal, Barros et al (2009) found that premix of mesosulfuronmethyl at 12 g ha -1 + iodosulfuron-methyl-sodium at 2.4 g ha -1…”
Section: Weed Control With Grass + Broadleaf Herbicidesmentioning
confidence: 99%
“…One such approach is the integrated weed management approach. New herbicide molecules like clodinafop propargyl, fenoxapropp-ethyl, Iodosulfuron-methyl sodium and mesosulfuron-methyl was very effective for weed control (Baghestani et al 2008 andBarros et al, 2009) [7,8] , Kumar et al, (2011) [13] , Singh et al, (2012) [9] and Malik et al (2013) [12] and Chitband et al, (2013) [14] reported the tank mixture of clodinafop + metsulfuron, mesosulfuron-methyl + Iodosulfuron-methyl-sodium and clodinafop + metsulfuron with and without surfactant provided excellent control of Phalaris minor, Avena fatua, Chenopodium album, Melilotus spp., Medicago denticulata, Vicia sativa, Rumex spp., Anagallis arvensis, Coronopus didymus, Lathyrus aphaca, Polygonum plebeium, sedges and many other weeds with higher grain yield of wheat. Avena fatua, Avena leudoviciana, Phalaris minor, Poa annua, and other common broad-leaf weeds are among the many annual grassy weeds that are said to be heavily infested in wheat.…”
Section: Introductionmentioning
confidence: 99%